Digitalization of Public Distribution System - Ms. A. Abirami, Muthulakshmi K, Pritheevi VA, Tamilselvan G (International Journal of Advanced Science and Technology, 2020)
The processes to avail items from the Ration shops are being complex nowadays due to excess crowd. The entire PDS works on ration cards. In order to overcome this difficulty, the mobile application named Online Ration System can be used. The commodities can be ordered online and payment can be made through online payment system in this application. Naive Bayes algorithm classifies the amount of commodities to be selected according to the members of the family. Once it is chosen and the payment is completed successfully, a set of time slots will be provided. Time slot and date to collect the items will be displayed. The commodities should be collected on the respective date and time slot. It also includes “Free Home Delivery” scheme for the senior citizens. Random Forest algorithm classifies the distance of delivery location. The distribution of commodities is completely supervised by the govt. It also has various disadvantages. The dealer tends to sell the commodities at a higher rate in the market. Due to this, we encounter a lack of transparency between the government and people. A good system has not been developed yet, by which the government is updates on the grain consumption by the people. This ration card management system works on android technology that replaces traditional ration cards.